PPP2R5C couples hepatic glucose and lipid Hhomeostasis - Cheng, Yong-Sheng; Seibert, Oksana; Klöting, Nora; Dietrich, Arne; Straßburger, Katrin; Fernández-Veledo, Sonia; Vendrell, Joan J.; Zorzano, Antonio; Blüher, Matthias; Herzig, Stephan; Berriel Diaz, Mauricio; Teleman, Aurelio A. (PLoS Genetics, 2015)
In mammals, the liver plays a central role in maintaining carbohydrate and lipid homeostasis by acting both as a major source and a major sink of glucose and lipids. In particular, when dietary carbohydrates are in excess, the liver converts them to lipids via de novo lipogenesis. The molecular checkpoints regulating the balance between carbohydrate and lipid homeostasis, however, are not fully understood. Here we identify PPP2R5C, a regulatory subunit of PP2A, as a novel modulator of liver metabolism in postprandial physiology. Inactivation of PPP2R5C in isolated hepatocytes leads to increased glucose uptake and increased de novo lipogenesis. These phenotypes are reiterated in vivo, where hepatocyte specific PPP2R5C knockdown yields mice with improved systemic glucose tolerance and insulin sensitivity, but elevated circulating triglyceride levels. We show that modulation of PPP2R5C levels leads to alterations in AMPK and SREBP-1 activity. We find that hepatic levels of PPP2R5C are elevated in human diabetic patients, and correlate with obesity and insulin resistance in these subjects. In sum, our data suggest that hepatic PPP2R5C represents an important factor in the functional wiring of energy metabolism and the maintenance of a metabolically healthy state.
Gesehen am 16.11.2020